METODE DAKWAH BERBASIS MEDIA SOSIAL ANALISIS MEDIA MCN AYA SOFYA - Rohman; Nadia Cahaya Amanda (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2025)
This study examines MCN Aya Sofya's digital da'wah strategy in reaching Muslim and non-Muslim communities through social media. Modern da'wah faces the challenge of reaching a wider audience, especially millennials and Gen Z who are active on social media. The study aims to analyze MCN Aya Sofya's digital da'wah application across various social media platforms. The research method employs a qualitative approach with literature review to analyze MCN Aya Sofya's digital da'wah strategies. Data was collected from MCN Aya Sofya's social media content and literature related to digital da'wah. The research findings indicate that MCN Aya Sofya implements a multi-platform dakwah strategy across five main platforms: YouTube (742,000 subscribers, 1,100 videos), Instagram, official website, Facebook, and TikTok. Each platform is optimized according to its audience characteristics. A hybrid approach combining conventional and digital methods enables MCN Aya Sofya to reach a diverse audience demographically and geographically. This digital dakwah strategy is effective in strengthening the faith of Muslims and providing an objective understanding of Islam to non-Muslims through testimonials from converts and constructive interfaith dialogue. MCN Aya Sofya proves that digital dakwah can be an effective medium for spreading the teachings of Islam peacefully in the modern era.